Servicification of manufacturing – evidence from Sweden. (1st January 2013) - Lodefalk, Magnus
There are signs that manufacturing is becoming increasingly focused on services; this process is known as servicification. Despite suggestive evidence, large gaps remain in our knowledge regarding this process. This paper contributes to closing these gaps by discussing the phenomenon, arriving at some conjectures and examining them empirically. Comprehensive datasets at both the firm and enterprise group level are developed for Sweden. Changes in manufacturing during the period from 1997 to 2006 are analysed in depth. The results show that manufacturing has been servicifying substantially. On the input side, services and qualified services are increasingly characteristic of in-house activity. On the output side, manufacturing has been accounting for an increasing share of services in total sales and exports. Moreover, we show that diversification is much greater (almost 60% higher) when all activities in the manufacturing industry's constituent enterprise groups are considered. The results imply that the practice of treating services and manufacturing separately – e.g., in trade policymaking – may be out-of-date. Finally, the findings illustrate the value of enterprise group-level data when studying structural economic changes.